INFLUENCE OF MINERAL NUTRITION ON THE YIELD OF BLACK OATS (AVENA STRIGOSA) IN THE CONDITIONS OF WESTERN UKRAINE - Mazurak І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article presents the findings from field studies conducted on dark gray podzolized soil regarding the yield of black oat grain, specifically focusing on how fertilizer rates affect production in the Western Forest-Steppe region of Ukraine. Four fertilizer treatments were examined: N60P20K40 (coontrol), N60P20K40 + S21, N60P20K40 + S21 + Mg26, N60P20K40 + S21 + Mg26 + microfertilizers (1.5 l/ha). In the control variant with N60P20K40 the mineral nutrition provided the highest seed germination rate at 83.7%. However, adding sulfur and magnesium resulted in a slight decrease in germination, with rates dropping to 80.6% and 80.7%, respectively. Interestingly, the survival rate of oat plants improved with the inclusion of a broader range of mineral nutrients, increasing from 88.6% in the control to 91.0% when sulfur, magnesium, and microfertilizers were applied. The application of the complete fertilizer package also resulted in the highest plant density before harvesting, averaging 436 plants per square meter. The research demonstrated that mineral fertilizers positively influence the yield of black oats, specifically the Black Prince variety. In the control variant, the oat yield was 4.90 tons per hectare. When sulfur was added ((N60P20K40 + S21), the yield increased by 4% to 5.10 tons per hectare. The introduction of magnesium in the third variant (N60P20K40 + S21 + Mg26) resulted in another 4% increase, bringing the yield to 5.32 tons per hectare, which is 0.42 tons per hectare higher than the control. In the fourth variant, where microfertilizers were applied during the tillering phase (N60P20K40 + S21 + Mg26 + microfertilizers at 1.5 l/ha), there was a notable enhancement in the absorption of macronutrients, improved plant resilience to stressors, and better grain quality. This change contributed to an additional 3% increase in yield compared to the previous variant, resulting in a total yield of 5.51 tons per hectare, which exceeds the control level by 0.61 tons per hectare.